Understanding the Nature of Science for Elementary School Students in Rural, Suburban, and Urban Areas - Cahyana Cahyana (Advanced Journal of STEM Education, 2025)
Understanding science is an important component of scientific literacy, which is the main goal of science learning. This understanding can improve students’ scientific literacy and enable them to achieve quality science learning outcomes. This research examines elementary school students’ understandings of the nature of science in three areas: rural, suburban, and urban. This research aims to analyze and describe elementary school students’ understanding of the nature of science in three different areas, which have an impact on students’ understanding of science processing, and using it in everyday life. The data were collected using quantitative methods with a type of survey research, where data were obtained using a questionnaire distributed to students in the form of Google Forms and analyzed using descriptive analysis. The participants in this research were 5th-grade elementary school students in rural, suburban, and urban areas, totaling 78 students with 26 students in each region. The results of data analysis show that students’ understanding of the nature of science in rural, suburban, and urban areas achieved satisfactory results. Students responded quite well to each statement in the questionnaire. Based on these results, it can be concluded that students in these three areas are good at processing knowledge and using it in everyday life. This research occurred in various geographic environments, namely rural, suburban, and urban. This research has a wider scope compared to previous research, which only focused on one area. The sample size in this research is limited, which affects the representativeness of the findings. In addition, the accuracy of a questionnaire depends on the wording, clarity, and reliability of the questions. Measurement errors can affect the quality of the data.